Strategies for developing memorization skills to enhance students learning resilience in the Asy-Syahrul Qur'any quarantine program - Athallah, Muh. Farhan; Salsabila, Saniya Alin; Maulana, Sahrul; Fauziyah, Ulil (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3731, 2025)
The Asy-Syahrul Qur'any quarantine program was created in response to the need for guidance amid the dual roles of tahfizh students as academics and memorizers of the Qur'an. However, in participating in the Asy-Syahrul Qur'any quarantine program, students are often faced with the challenge of managing stress and maintaining motivation to study. This condition requires strategies that can improve the learning resilience of tahfizh students. This article aims to describe tahfizh coaching strategies that can improve the learning resilience of students in the Asy-Syahrul Qur'any quarantine program.  The method used is qualitative. The data collection techniques used are interviews, observation, and documentation. The results of the study show that there are four tahfizh coaching strategies to improve learning resilience, including spiritual strengthening, time management, social support, and religious coping. Ultimately, future research is expected to examine the effectiveness of these four strategies in supporting the improvement of tahfizh students' learning resilience in the digital era.